Enabling interprofessional collaboration in delirium management / Interprofessionelle Zusammenarbeit im Delir-Management gestalten - Moser Andrea; Grosse Uta; Lauener Susanne Knüppel (Sciendo, 2020)
Interprofessional collaboration (IPC) is dependent on different expectations and communication styles. IPC is a meaningful approach to accomplish treatment goals, especially in patients with delirium. Delirium affects approximately 50 % of patients older than 65 years in acute care settings. The constant attention and effort needed to care for patients suffering from delirium is challenging and cannot be provided by one profession alone. Instead, there is a need for IPC.